Trade, External Shock And Economic Growth In Selected Asean And South Korean Economies - Masron, Tajul Ariffin (2006)

(untitled)
This study examines the impact of trade on economic growth through four main growth channels, namely private domestic investment (PDI), government spending (GOV), manufacturing value added (MVA) and foreign direct investment (FDI), taking into consideration the role of external shock, which is proxied by capital flight. It is particularly important because past studies indicate that trade and economic growth does not show a parallel co-movement, or in other words, high level of trade does not necessarily lead to high economic growth. By using five East Asian economies (i.e. Indonesia, Korea, Malaysia, The Philippines and Thailand) as case studies, autoregressive distributed lag (ARDL) estimation procedure is utilized in order to estimate the impact of trade on economic growth which covers period from 1970 to 2002. The indirect impact procedure is used so as to help us to determine through which channel trade will positively affect economic growth, vice versa. The indirect impact of trade on economic growth is calculated based on the study done by Wacziarg (2001).Several important conclusions can be drawn from the study. The threat of capital flight (and thus negative external shock) is justified in this study. Capital flight could reverse the good prospect of economic growth as had been experienced by five East Asian economies during the 1997 economic crisis. In addition, the calculated indirect impact of trade on economic growth tells us the reason of why trade does not necessarily lead to high economic growth since the indirect impact does not necessarily positive and high through all channels. The main source of low positive or negative effect of trade on economic growth is because of inefficiency in resource allocation (proxied by channels of PDI and GOV) as well as low technological development (proxied by channels of MVA for domestic technological development and FDI for foreign technological diffusion) in East Asian, especially in the case of ASEAN economies. What is important to mention here is that without considering the indirect impact of trade on growth, we may face difficulty to magnify the positive impact of trade on economic growth since we are not guided as to what effort should be undertaken. Based on the framework in this study, we found that in order for ASEAN to emulate the success of Korea in developing its economy, ASEAN has to ensure that they are moving towards greater competitiveness by enhancing the level of efficiency as well as technological development.